(untitled) - Aamir Khan; Minhas Majeed Khan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This paper examines India and Pakistan geopolitical and geo-economic interests in post 9/11 Afghanistan. The state of Afghanistan possesses geo-political and geo-economic opportunities and challenges for both the state. The rivalry and competition between the two South Asian neighbours are shaping in the state of Afghanistan. The Geo-political and geo-economic interests of both states are in divergence with each other. The fault lines of competition between India and Pakistan are transformed to geo-economic influence in Afghanistan and beyond. The state of Afghanistan represents a land bridge and potential energy corridor for India and Pakistan. Therefore, this study highlights the divergent geo-economic interests along with geo-politics in Afghanistan. It is argued that geo-economic has emerged as a new pattern of rivalry between India and Pakistan in Afghanistan. Both states is using geo-economic along with geo-political parameters and interests in a spiral context and reinforcing themselves with the evolving scenarios.